Perspectives in linear accelerator for FLASH VHEE: Study of a compact C-band system. (December 2022) - Faillace, L.; Alesini, D.; Bisogni, G.; Bosco, F.; Carillo, M.; Cirrone, P.; Cuttone, G.; De Arcangelis, D.; De Gregorio, A.; Di Martino, F.; Favaudon, V.; Ficcadenti, L.; et al.
Abstract: Purpose: In order to translate the FLASH effect in clinical use and to treat deep tumors, Very High Electron Energy irradiations could represent a valid technique. Here, we address the main issues in the design of a VHEE FLASH machine. We present preliminary results for a compact C-band system aiming to reach a high accelerating gradient and high current necessary to deliver a Ultra High Dose Rate with a beam pulse duration of 3 μ s . Methods: The proposed system is composed by low energy high current injector linac followed by a high acceleration gradient structure able to reach 60–160 MeV energy range. To obtain the maximum energy, an energy pulse compressor options is considered. CST code was used to define the specifications RF parameters of the linac. To optimize the accelerated current and therefore the delivered dose, beam dynamics simulations was performed using TSTEP and ASTRA codes. Results: The VHEE parameters Linac suitable to satisfy FLASH criteria were simulated. Preliminary results allow to obtain a maximum energy of 160 MeV, with a peak current of 200 mA, which corresponds to a charge of 600 nC. Conclusions: A promising preliminary design of VHEE linac for FLASH RT has been performed. Supplementary studies are on going to complete the characterization of the machine and to manufacture and test the RF prototypes. Highlights: Novel modality for radiotherapy reduces healthy tissue toxicities; the FLASH effect. FLASH irradiation is obtained with ultra-high dose-rate short bursts. Linear accelerator-based machine is designed for FLASH experiments. Small footprint laboratory for very-high energy electron for pre-clinical studies.